A qualitative study assessing the acceptability and adoption of implementing a results based financing intervention to improve maternal and neonatal health in Malawi. Issue 1 (December 2016) - Wilhelm, Danielle; Brenner, Stephan; Muula, Adamson; De Allegri, Manuela
Abstract Background Results Based Financing (RBF) interventions have recently gained significant momentum, especially in sub-Saharan Africa. However, most of the research has focused on the evaluation of the impacts of this approach, providing little insight into how the contextual circumstances surrounding the implementation have contributed to its success or failure. This study aims to fill a void in the current literature on RBF by focusing explicitly on the process of implementing a RBF intervention rather than on its impact. Specifically, this study focuses on the acceptability and adoption of the RBF intervention's implementation among local and international key stakeholders with the aim to inform further implementation. Methods The Results Based Financing for Maternal and Neonatal Health (RBF4MNH) Initiative is currently being implemented in Malawi. Our study employed an exploratory cross-sectional qualitative design to explore the factors affecting the acceptability and adoption of the intervention's implementation. Purposeful sampling techniques were used to identify each key stakeholder who participated in all or parts of the implementation process. In-depth interviews were conducted and analyzed using a deductive open coding approach. The final interpretation of the findings emerged through active discussion among the co-authors. Results Despite encountering several challenges, such as delay in procurement of equipment and difficulties in arranging local bank accounts, all stakeholders responded positively to the RBF4MNH Initiative. Stakeholders' acceptance of the RBF4MNH Initiative grew stronger over time as understanding of the intervention improved and was supported by early inclusion during the design and implementation process. In addition, stakeholders took on functions not directly incentivized by the intervention, suggesting that they turned adoption into actual ownership. All stakeholders raised concerns that the intervention may not be sustainable after its initial program phase would end, which contributed to hesitancy in fully accepting the intervention. Conclusions Based on the results of this study, we recommend the inclusion of local stakeholders into the intervention's implementation process at the earliest stages. We also recommend setting up continuous feedback mechanisms to tackle challenges encountered during the implementation process. The sustainability of the intervention and its incorporation into national budgets should be addressed from the earliest stages.